Juridic Analysis of Implementation of Resolving Criminal Acts of Fraud Through Restorative Justice (Study of Directorate of General Criminal Investigation of the Riau Islands Police) - Reni Nanda; Laily Washliati; Erniyanti; Soerya Respationo (MultiTech Publisher, 2023)
The police are law enforcement agencies that are given the authority to carry out investigations and investigations of criminal acts which are then faced with legal developments in the form of the concept of resolving criminal cases using restorative justice which aims to provide legal certainty, benefit, and justice. Therefore, this study aims to find out how the legal arrangements, implementation, and constraint factors as well as solutions related to the application of a Restorative Approach to the Settlement of Criminal Cases by the Directorate of General Criminal Investigation of the Riau Islands Police are made. This study uses empirical legal research (field) using a normative juridical approach, namely in the form of an analysis of the legal arrangements that regulate matters that become problems to obtain secondary data, and a sociological juridical approach to obtain primary data through field research. The results of this study indicate that the legal arrangements in this writing are the Circular Letter of the Chief of Police Number SE/8/VII/2018 concerning the Application of Restorative Justice in the Settlement of Criminal Cases, the Regulation of the Chief of Police Number 6 of 2019 concerning Investigation of Criminal Acts Article 12 and the State Regulation of the Republic of Indonesia Number 8 2021 on Handling Crimes Based on Restorative Justice.